Spectrum of morbid anatomy of liver in autopsy cases - Kataria, Sant P.; Singh, Narender; Kumar, Sanjay; ., Mamta; Khanagwal, Vijaypal (International Journal of Research in Medical Sciences, 2021)
Background: Purpose of autopsy is to learn the truth about the person’s health during and how the person died. Thus, autopsy study provides valuable information about the disease. The main aim of the study was to know the spectrum of morbid anatomical changes in liver autopsy. Methods: A prospective study was carried out on 100 liver specimens of autopsy cases comprising of 37 cases of roadside accidents, 17 of poisoning, 13 of burns, 10 of chronic illness, 7 each of hanging and head injury, 4 of myocardial infarction and 5 of death due to miscellaneous causes. Representative microsections of liver were evaluated for histopathological parameters like congestion, ballooning degeneration, hepatocellular necrosis, sinusoidal dilation, fatty change, bile stasis, fibrosis, lobular inflammation and portal inflammation. Results: Out of total 100 cases, 77 were males and 23 females. Male to female ratio was 3.34:1. Hepatomegaly was seen in 15% of cases. Chronic venous congestion was the main histopathological diagnosis seen in 61% of the cases followed by chronic hepatitis in 12%, normal liver histology in 9%, hepatic steatosis and cirrhosis in 6%, granulomatous hepatitis in 2%, and sinusoidal congestion, portal triaditis and secondary neoplasm in 1% each. Conclusions: Chronic venous congestion, chronic hepatitis, cirrhosis and hepatic steatosis were the common liver diseases identified. Autopsy study is useful to monitor the cause of death and to plan medical strategy. Histopathological examination of the liver is specialized learning tool to study the various diseases of liver which is a great value in improving the diagnosis.